Peran Motivasi Belajar Siswa Terhadap Hasil Belajar Pada Muatan IPS (Studi di SD Negeri 067245 Medan Selayang) - Risa Damira; Daulat Saragi (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
This study aims to determine how the role of learning motivation on student learning outcomes in social studies class VI SD Negeri 067245 Medan Selayang. This type of research is descriptive research. The subjects of this study were all Grade VI students at SD Negeri 067245 Medan Selayang. This research method is a literature review (Library Research). Collecting data using observation, interviews and documentation. Data analysis techniques using descriptive analysis techniques. Based on the results of this study, it shows that: The Role of Student Learning Motivation on learning outcomes in Social Science Subjects in Theme 6 (Towards a Prosperous Society) Sub-Theme II (Building a Prosperous Society) Class VI SD Negeri 067245 Medan Selayang is very important, this is because students Those who have great motivation will be more active in learning, enthusiastic, solving problems, more active during the teaching and learning process, high curiosity and so on so that they can improve their learning outcomes. This can be seen when students are studying on the theme of Theme 6 (Towards a Prosperous Society) Sub Theme II the teacher increases student motivation by using interesting learning methods and media with the aim of attracting students' attention. Conversely, students who have low motivation, appear indifferent, easily discouraged, their attention is not focused on learning, as a result students will experience learning difficulties. It can be seen that there are still students in class VI who cannot be independent and responsible, especially in social studies learning.